Cannabinoid type-2 receptors: An emerging target for regulating schizophrenia-relevant brain circuits - Ferranti, Anthony S.; Foster, Daniel J. (Frontiers in Neuroscience, 2022)
Although the cannabinoid type-2 receptor (CB2) is highly expressed in the immune system, emerging evidence points to CB2 playing a key role in regulating neuronal function in the central nervous system. Recent anatomical studies, combined with electrophysiological studies, indicate that CB2 receptors are expressed in specific dopaminergic and glutamatergic brain circuits that are hyperactive in schizophrenia patients. The ability of CB2 receptors to inhibit dopaminergic and hippocampal circuits, combined with the anti-inflammatory effects of CB2 receptor activation, make this receptor an intriguing target for treating schizophrenia, a disease where novel interventions that move beyond dopamine receptor antagonists are desperately needed. The development of new CB2-related pharmacological and genetic tools, including the first small molecule positive allosteric modulator of CB2 receptors, has greatly advanced our understanding of this receptor. While more work is needed to further elucidate the translational value of selectively targeting CB2 receptors with respect to schizophrenia, the studies discussed below could suggest that CB2 receptors are anatomically located in schizophrenia-relevant circuits, where the physiological consequence of CB2 receptor activation could correct circuit-based deficits commonly associated with positive and cognitive deficits.